Chemical constituents of Euphorbia hyberna L. (Euphorbiaceae) - Ferreira, Ana Margarida V. D. (2022)
Chemical investigation of the aerial part and the roots of Euphorbia hyberna L. subs. hyberna. resulted in the isolation and identification of four triterpenoids (3-O-octadecanoyllupeol (1), glut-5-en-3-ol (2), 24-methylenecicloartan-3-ol (3) and cicloart-23-ene-3,25-diol (6)) along with the phenolic compounds ellagic acid (4) and 3,30 -di-O-methylellagic acid (7). Although these are all known compounds, this is the first report of their isolation from this plant. Their structures were elucidated on the basis of spectral methods, including 2D NMR experiences, and confirmed by comparing with the literature data.